A REVISION OF MALESIAN CAESALPINIA, INCLUDING MEZONEURON*(LEGUMINOSAE-CAESALPLNIACEAE) - T. A. HATTINK (Research Center for Biology, 1974)
This is the first taxonomic revision of this pantropical genus of prickly climbers for the area, the Solomons inclusive.It deals with 21 species, of which 19 ore native (dealt with over the whole of their area),and 2 are widely naturalized, viz C. pulckerrima and C. sappan.Also mentioned are 3 occasional introductions. Full descriptions are given,keys to the native and to the cultivated species, the complete synonymy and typification with all important later references.Many new deductions have been made,some from adjacent regions. New species are C. opptrsitifolia, from Borneo, with truly opposite leaves and C Bolomonewsis from the Solomons; new combinations are C.andamanica based on Mezoneuron andamanicum Prain,C furfuracea based on M. furfuraceum. Prain, C. hymenocarpa based on M, hymeno carpum Prain,C latisiliqua based on latisiliquum (Cavan) Merr,C. mindorensis based on M. mindorense Merr., C. pubeecens based on M. pubescens Desf., C. scorteckinii baaed on M. scortechinii F.v.M. from Queensland and now on record from New Guinea, the last one closely resembling C. brachycarpa, another new combination based on M. braehycarpmn Benth, from New South Wales.No subdivisions of the genus are adopted or proposed. The long standing nomenclatural confusion hetween C. bonduc, C. bonducella,C. cristrt, and C. major has been visualized in a diagram. Specimens of importance for the knowledge of the area have been cited. Extreme and intergrading specimens are discussed. Eeference is made to the main ecomonic literature Indexes to all names and all specimens are given.